Dinamika fear of missing out dalam perilaku konsumtif generasi Z - Gladys Carissa Ardhany; Niken Titi Pratitis; Isrida Yul Arifiana (PSYCOMEDIA : Jurnal Psikologi, 2026)
The development of social media and the ease of digital transactions have contributed to consumptive behavior among Generation Z, particularly through the phenomenon of fear of missing out. This study aims to examine Fear of Missing Out as a driver of consumptive behavior among Generation Z. A quantitative approach with a correlational design was employed. The participants were working Generation Z individuals aged 18 to 28 years who reside in Surabaya City. Data were collected using a Fear of Missing Out scale and a consumptive behavior scale based on a Likert format. Data analysis was conducted using a nonparametric correlation technique. The results indicate that Fear of Missing Out is significantly associated with consumptive behavior, particularly in unplanned purchasing, emotional responses to promotions, and pressure to follow trends. These findings suggest that fear of missing out functions as a psychological factor that encourages consumptive behavior among Generation Z. This study concludes that managing fear of missing out is essential in fostering more rational and adaptive consumption behavior. By addressing this psychological aspect, marketers and educators can develop strategies that promote healthier spending habits and encourage mindfulness in purchasing decisions. Future research should explore intervention methods that mitigate the effects of fear of missing out on consumer behavior, aiming to support Generation Z in making more informed choices.